2020
DOI: 10.1017/cjn.2020.173
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Neuropsychiatric Impacts of COVID-19 Pandemic

Abstract: Background: Albeit primarily a disease of respiratory tract, the 2019 coronavirus infectious disease (COVID-19) has been found to have causal association with a plethora of neurological, neuropsychiatric and psychological effects. This review aims to analyze them with a discussion of evolving therapeutic recommendations. Methods: PubMed and Google Scholar were searched from 1 January 2020 to 30 May 2020 with the following key terms: “COVID-19”, “SARS-CoV-2”, “pandemic”, “neuro-COVID”, “s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
186
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 154 publications
3
186
1
4
Order By: Relevance
“…neuropathogenesis is autoimmune, which would align with steroid responsiveness. The finding of the claustrum sign on brain MRI, not previously reported in a COVID-19 patient, [4][5][6][7][8] provides further support for the idea that acute SARS-CoV-2 infection may present as an autoimmune encephalitis.…”
supporting
confidence: 65%
“…neuropathogenesis is autoimmune, which would align with steroid responsiveness. The finding of the claustrum sign on brain MRI, not previously reported in a COVID-19 patient, [4][5][6][7][8] provides further support for the idea that acute SARS-CoV-2 infection may present as an autoimmune encephalitis.…”
supporting
confidence: 65%
“…Physicians are seeing increasingly more patients with a spectrum of neurological manifestations associated with coronavirus disease 2019 (Ghosh et al 2020;Gutiérrez-Ortiz et al 2020;Rábano-Suárez et al 2020;Roy et al 2020). However, the pathogenesis of COVID-19-induced neurological manifestations is still in its infancy.…”
mentioning
confidence: 99%
“…Discussion SARS-CoV-2 has potential for neurotropism (Li et al 2020;Rábano-Suárez et al 2020;Roy et al 2020). Study with animal models have demonstrated that SARS-CoV and MERS-CoV, possibly via olfactory nerves, can spread rapidly inside central nervous system, thalamus and brainstem in particular (Li et al 2020).…”
mentioning
confidence: 99%
“…Neurological outcomes in patients with COVID-19 have been reported [5]. The neurological manifestations range from headache, dizziness, confusion, to in a few cases, more severe conditions, such as encephalopathy, acute disseminated encephalomyelitis and GBS, among others [6].…”
Section: Discussionmentioning
confidence: 99%